Research and Practical Application of Digital Technology-Based Paperless Order Tracking Methods for Clothing - Ji, Enfeng (Journal of Research in Science and Engineering, 2025)
Objective: This paper aims to explore paperless order tracking methods based on information technology, construct an efficient, collaborative, and traceable clothing order management system, and promote enterprise digital transformation and enhance industry competitiveness. Methods: This study uses case analysis methods, combining digital technologies such as ERP systems, 3D modeling, mobile applications, and QR code recognition to analyze typical enterprise practices and discuss the technical, personnel, and management challenges involved in implementation. Conclusions: 1) The paperless order tracking process built on information systems not only significantly improves operational efficiency and market response speed within the enterprise but also enhances the transparency and traceability of information transmission. 2) This method has positive implications for promoting the digital and green transformation of the apparel industry and provides strong support for enterprises to address the complexity and uncertainty of future market environments.